Is Banks' Home Bias Good or Bad for Public Debt Sustainability? - Asonuma, Tamon (IMF Working Papers; Working Paper, 2015)
Motivated by the recent increase in domestic banks' holdings of domestic sovereign debt (i.e., home bias) in the European periphery, this paper analyzes implications of banks' home bias for the sovereign's debt sustainability. The main findings, based on a sample of advanced (AM) and emerging market (EM) economies, suggest that home bias generally reduces the cost of borrowing for AMs and EMs when debt levels are moderate to high. A worsening of market sentiments appears to dimish the favorable impact of home bias on cost of borrowing particularly for EMs. In addition, for AMs and EMs, higher home bias is associated with higher debt levels, and less responsive fiscal policy. The findings suggest that home bias indeed matters for debt sustainability: Home bias may provide fiscal breathing space, but delays in fiscal consolidation may actually delay problems until debt reaches dangerously high levels.